2004
DOI: 10.1016/j.eurpsy.2004.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of present and past antipsychotic side effects on attitude toward typical antipsychotic treatment and adherence

Abstract: All antipsychotic side effects, present or past, can have a durable negative impact on patient's attitude toward antipsychotic treatment and adherence. Non-adherence is mainly determined, among other factors, by these negative attitudes, which are partly influenced by the experience of past or present antipsychotic-induced side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
168
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(184 citation statements)
references
References 40 publications
6
168
2
3
Order By: Relevance
“…Study done by Hamburg indicated that patients presenting with side effect compared with patients without side effect had a significantly more negative general attitude toward antipsychotics and were less likely to be encouraged to take such a medication in case of need [22]. Similarly another study indicated patient having extra pyramidal and psychic side effects and sedation were found to be statistically significantly associated with non-adherence [23].…”
Section: Discussionmentioning
confidence: 99%
“…Study done by Hamburg indicated that patients presenting with side effect compared with patients without side effect had a significantly more negative general attitude toward antipsychotics and were less likely to be encouraged to take such a medication in case of need [22]. Similarly another study indicated patient having extra pyramidal and psychic side effects and sedation were found to be statistically significantly associated with non-adherence [23].…”
Section: Discussionmentioning
confidence: 99%
“…Movement disorders secondary to antipsychotics constitute a major reason for non-compliance, which results in an increased risk of psychotic relapse (Robinson et al 2002;Lambert et al 2004;Casey, 2006).…”
mentioning
confidence: 99%
“…[32] On evaluating medication-related factors, this study found that there was a significant association between the complexity of medication schedule, side effects of drugs, ineffectiveness of medications on one hand and non-adherence on the other hand. Similarly, ineffectiveness of medication against psychotic or negative symptoms [31] and side effects [30,37,38] were identified as risk factor This sensation of ineffectiveness of antipsychotic drugs is due to their delayed onset of the therapeutic effects (while adverse effects appear earlier). [30] The role of complexity of medication schedule, as a risk factor of non-adherence was a subject of controversy between the different studies.…”
Section: Discussionmentioning
confidence: 99%